2008
DOI: 10.1021/pr700844z
|View full text |Cite
|
Sign up to set email alerts
|

Different Signaling Pathways Expressed by Chicken Naïve CD4+ T Cells, CD4+ Lymphocytes Activated with Staphylococcal Enterotoxin B, and Those Malignantly Transformed by Marek’s Disease Virus

Abstract: Proteomics methods, based on liquid chromatography and tandem mass spectrometry, produce large "shotgun" proteomes that are most appropriately compared not at the level of differentially expressed proteins only but at the more comprehensive level of biological networks and pathways. This is now possible with the emergence of functional annotation databases and tools, databases of canonical pathways and molecular interactions and computational text mining tools. Here, we used shotgun proteomics, and the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Ingenuity Pathway Analysis ( http://www.ingenuity.com, IPA)-based functional grouping of the significantly expressed pathways (data not shown) confirmed our previous findings [26] that PCD was perturbed and integrin signaling was increased in CD30 hi cells. IPA analysis also indicated that PCD signaling, molecular mechanisms of cancer, NF-κB activation by viruses, p53 signaling, PPARα/RXRα activation, PTEN signaling, BRCA1 in DNA damage, VEGF signaling, Wnt/β-catenin signaling, lymphotoxin β receptor signaling (important in non-canonical NF-κB activation pathway induction), TGF-β signaling (insensitivity to antigrowth signals) and nitric oxide signaling (important in angiogenesis) were activated in both CD30 hi and CD30 lo cells.…”
Section: Resultssupporting
confidence: 87%
“…Ingenuity Pathway Analysis ( http://www.ingenuity.com, IPA)-based functional grouping of the significantly expressed pathways (data not shown) confirmed our previous findings [26] that PCD was perturbed and integrin signaling was increased in CD30 hi cells. IPA analysis also indicated that PCD signaling, molecular mechanisms of cancer, NF-κB activation by viruses, p53 signaling, PPARα/RXRα activation, PTEN signaling, BRCA1 in DNA damage, VEGF signaling, Wnt/β-catenin signaling, lymphotoxin β receptor signaling (important in non-canonical NF-κB activation pathway induction), TGF-β signaling (insensitivity to antigrowth signals) and nitric oxide signaling (important in angiogenesis) were activated in both CD30 hi and CD30 lo cells.…”
Section: Resultssupporting
confidence: 87%
“…SEB can cross-link major histocompatibility complex class II molecules on the antigen-presenting cell with the β chain of the T cell receptor and activate vigorous fractions of the T cell population at high frequency [2, 3], which has no need of classical processing and presentation of antigen [4]. The immune response of T cells to SEB displays a biphasic change [5, 6] which consists of an early activation presented as T cell proliferation and a second anergy due to apoptosis of the appropriate T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we observed a median survival of 36 days (mock) and 55 days (IFNγ). It has been shown that MDV tumor tissue contains elevated levels of interferon-induced proteins, amongst them IFNγ-inducible protein 30 (IFI30), which has been discussed to possess antitumor properties [39,40]. Hence, IFNγ could not only inhibit MDV replication, but also induce an antitumor response [41].…”
Section: Effect Of Ifnγ On MDV Replication and Pathogenesismentioning
confidence: 99%